Antibacterial and Anti-biofilm Efficacy of Chinese Dragon’s Blood Against Staphylococcus aureus Isolated From Infected Wounds - Zheng, Xiangkuo; Chen, Lijiang; Zeng, Weiliang; Liao, Wenli; Wang, Zhongyong; Tian, Xuebin; Fang, Renchi; Sun, Yao; Zhou, Tieli (Frontiers in Microbiology, 2021)
Chinese dragon’s blood (CDB), a characteristic red resin, is an important traditional Chinese medicine (TCM), and empiric therapy of infected wounds with CDB is performed in clinical settings. For the first time, we herein report the antibacterial and anti-biofilm efficacy of CDB against Staphylococcus aureus (S. aureus). Antimicrobial susceptibility testing, growth curve assay, time-kill curve assay, crystal violet biofilm assay, scanning electron microscope (SEM) analysis, cell membrane tests, and quantitative real-time polymerase chain reaction (qRT-PCR) were used for this purpose. The results suggested that the minimum inhibitory concentration (MIC) values of CDB against S. aureus ranged from 32 to 128 µg/mL. Growth curves and time-kill curves confirmed that CDB could inhibit the growth of S. aureus. The biofilm formation ability and the expression levels of saeR, saeS, and hla of S. aureus in the presence and absence of CDB were statistically significant (P < 0.01). The results of SEM analysis and cell membrane tests revealed that exposure to CDB had some destructive effects on S. aureus cells. In conclusion, CDB exhibits positive antibacterial activity against S. aureus. Moreover, CDB could reduce the biofilm formation and the virulence factors of S. aureus by downregulating the expression levels of saeR, saeS, and hla genes. These findings indicated that CDB has immense potential to serve as a viable alternative for the treatment of infected wounds caused by S. aureus in clinical settings.